Medical treatment and ramadan fasting amongst Malaysian muslim medical staff / Che Noriah Othman and Mohd. Marzuk Shaary - Othman, Che Noriah (Faculty of Architechture , Planning & Surveying, 2011)
Introduction: The level of knowledge about Ramadan fasting and medical treatment amongst Medical staff has not been documented. This study assessed the level of knowledge amongst Malaysian Muslim Medical staff regarding this issue. Methodology: Questionnaires were distributed to 24 Muslim Medical Staff volunteers. The level of knowledge was evaluated based on the percentage of correct answers given by the respondents. Results: Most of the respondents understood that the use of inhaler, drip infusion, injection, ear, eye and nose drops and the use of sublingual tablets for medical purposes do not break the fast. Conclusion: The majority of respondents are knowledgeable on the issue of Ramadan fasting and Medical treatment.